Successful treatment of corrosive esophageal atresia in a child using combined antegrade-retrograde dilation: a case report - Wu, Hao; Jiang, Xiaohan; Wang, Zhiqi; Liu, Li; Mo, Xuming; Fan, Zhining (Frontiers in Pediatrics, 2026)
Corrosive esophageal injury in children may rarely lead to complete atresia. No standardized treatment exists for pediatric corrosive esophageal atresia. This case demonstrates a novel minimally invasive approach. A 12-year-old male developed complete esophageal atresia after accidental ingestion of industrial alkali. He underwent combined antegrade-retrograde endoscopic dilation (CARD) with balloon dilation and covered stent placement. Oral feeding resumed by postoperative day two, and at three-month follow-up, he reported normal eating without complications. To our knowledge, this represents the first reported use of CARD for pediatric corrosive esophageal atresia, demonstrating it as a feasible and effective minimally invasive alternative to surgery in selected cases.